Turning Points The Nature of Creativity - Chen, Chaomei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
"Turning Points: The Nature of Creativity" discusses theories and methods focusing on a critical concept of intellectual turning points in the context of critical thinking, scientific discovery, and problem solving in general. This book introduces a novel analytical and experimental system that provides not only new ways for retrospective studies of scientific change but also for characterizing transformative potentials of prospective scientific contributions. The book is intended for scientists and researchers in the fields of information science and computer science. Dr. Chaomei Chen is an Associate Professor at the College of Information Science and Technology, Drexel University, USA.
Turning Points -- Saliency and Novelty -- Informetics -- Visual Analytics -- Case Studies -- Research Agenda.
Keywords: Computer science; Science -- Philosophy; Information systems; Science -- Study and teaching; Humanities; Library science; Computer Science; Information Systems and Communication Service; Philosophy of Science; Science Education; Interdisciplinary Studies; Library Science